RECONSTRUCTION OF LEGAL CULTURE OF POLITICAL PARTY IN RECRUITMEN OF LEGISLATIVE MEMBERS WITH GENDER EQUALITY - Baharudin Baharudin (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
The legal culture of political parties in the recruitment of legislativecandidates with gender law in Bandar Lampung City is based on a